Development of STEM-based Earthquake Mitigation Educational Media for High School Students' Learning - Yusofa, Devis; Lukma, Hazairin Nikmatul (Universitas Islam Balitar, 2025)
Knowledge about earthquake disaster mitigation is mandatory, so the government includes this material in the education curriculum. Earthquake educational media based on science, technology, engineering, and mathematics (STEM) is considered capable of supporting learning that encourages students to be active, creative, and innovative in completing STEM-based experimental projects so that it can improve students' understanding of the material. The purpose of this study was to determine the effect of developing educational teaching media in the form of teaching aids equipped with STEM-based earthquake mitigation learning e-modules on the learning outcomes of students at SMAN 2 Blitar. The research method used in this study is research and development (R&D) with the analysis, design, development, implementation, and evaluation (ADDIE) development model. Data was collected from needs analysis, module validation, response, and student learning outcomes. The results of the T-test showed a significant difference, namely an increase in student learning outcomes, in classes that received learning with STEM-based educational media.